Dimensional Changes of Glass Ionomers and a Giomer during the Setting Time - Jelena Spajić; Katica Prskalo; Kristina Šariri; Matej Par; Vlatko Pandurić; Nazif Demoli (University of Zagreb. School of Dental Medicine, 2018)
Objectives: The aim of this study was to evaluate dimensional changes of conventional glass ionomer cements, resin-modified glass-ionomer cement, and a giomer during the setting time using digital laser interferometry. Additionally, the influence of different curing modes ("high", "soft", and "low") of a light-emitting diode (LED) curing unit on dimensional changes was evaluated. Materials and methods: Linear curing shrinkage of conventional glass ionomer cements (CGICs): Fuji IX Extra (F9E), Fuji IX Fast (F9F), Ketac Molar Aplicap (KM), Ketac Molar Quick Aplicap (KMQ), resin-modified glass ionomer cement (RM GIC): Fuji II LC (F2LC) and giomer: Beautifil II (B2) was analyzed. All tested materials were of shade A3, while all of the GIC were encapsulated. Discoid specimens (n=10, d=10 mm, h=0.85 mm) were prepared for each tested material and each curing mode (for light-curable materials) according to the manufacturer's instructions. Light-curable specimens were cured with LED curing unit (Bluephase G2, Ivoclar-Vivadent, and Schaan, Liechtenstein). Dimensional changes during curing were recorded in real-time. The results were analyzed by ANOVA, and Tukey post hoc test was used for multiple comparisons (α < 1%). Results: All tested materials showed an initial setting expansion and a subsequent setting shrinkage. KM and KMQ had significantly lower setting shrinkage than RM GIC polymerized using any of the three curing modes. B2 showed lower shrinkage compared to F2LC. Conclusions: The extent of curing shrinkage in RM GIC measured in this study can affect longevity of restorations.